Analisis Perubahan Premi Bruto Industri Asuransi Indonesia - Heri Sasono; Nurhanan Said (Global Leadership Organizational Research in Management, 2024)
Insurance premium income needs to be maintained by business people, because it is the main performance that must be maintained and improved. This study looks at whether macro variables, such as; Inflation, economic growth and the dollar exchange rate affect changes in gross insurance premiums in Indonesia. The peneriode of this study for 15 years from 2008 to 2022 with correlation, regression, coefficient of determination analysis as well as t test and anova test (F test) by using SPSS software version 22. The results showed that the inflation rate, economic growth and the dollar exchange rate, had a significant effect simultaneously, while partially the variable of economic growth did not contribute significantly to gross insurance premiums in Indonesia with a coefficient of determination of 88.5% was very strong.